Curriculum development: Preparing trainees to care for children and adolescents with psychiatric disorders. (July 2015) - Foley, Kimberly P; Haggerty, Treah S; Harrison, Natasha
Family physicians provide care for about one-third of the children and adolescents in the United States, many of whom present with psychological concerns. Family physicians often do not recognize these psychological disorders and therefore do not diagnose or treat them. This report describes the implementation of a curriculum designed to increase family medicine trainees' level of awareness that children/adolescents experience psychiatric conditions. This goal is achieved through the addition of a clinical child/adolescent psychologist faculty member, resident self-assessment of training needs and subsequent development of didactic presentations to address these needs. The curriculum relies on the acquisition of child/adolescent psychiatric screeners, development of child/adolescent-focused bibliotherapy materials, and the development of a longitudinal behavioral sciences curriculum. To facilitate the screening of child/adolescent psychiatric disorders, a comprehensive collection of age-appropriate psychiatric screeners were compiled and made readily available in all precepting areas. To assist with the identification of specific child/adolescent psychiatric deficit areas, family medicine resident physicians were presented with an inventory of child/adolescent psychiatric, psychosocial, and behavioral topics, based upon American Academy of Family Practice guidelines and Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition psychiatric disorders, and self-selected training deficiencies.